Implementation of National Health Insurance (JKN) Program in Konawe District - Sumail, Sulastian Manikam (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
National Health Insurance (JKN) is a part of National Social Insurance Systems (SJSN) held through social health insurance mechanism which is required (mandatory) aiming to satisfy appropriate main health need, given to those who already paid the premium or being paid by government. This study aimed to describe implementation of JKN program in Konawe district in 2014 in term of socialization, participation, health facility readiness, and referral system, using phenomenological approach through indepth interview, observation and documentation. The data were gained from 6 key informants and other 7 common informants who directly involved in implementing JKN program. The result of the study showed that implementation of JKN program socialization in Konawe district was already done by BPJS, health department, hospital, and public health center through some mass and electronic media, either directly or indirectly. In term of BPJS participation, it reached 53.31% of inhabitants already both of PBI membership and non PBI membership and will be increasing due to cooperation between central and district government in order all society will be covered by JKN program. The health facility readiness generally all health service providers, either hospital or public health centers supported by health department were ready to implement JKN, including facility, infrastructure, and human resources and keep increasing the quality of service. The referral system used in health services was already referred to health ministry regulation about gradually referral system, where society has to take medical check at primary health services firstly.  Keywords: JKN, BPJS,  Socialization, Participation, Health facility readiness, Referral system.